2021
DOI: 10.3389/fpsyg.2021.756297
|View full text |Cite
|
Sign up to set email alerts
|

Involvement Modulates the Effects of Deception on Memory in Daily Life

Abstract: Previous studies have demonstrated that liars who adopt a false denial strategy often forget what they lied about, which has been labeled the denial-induced forgetting (DIF) effect. However, several investigations have not found such an effect. It has been suggested that involvement might play a role in the inconsistency. The present study was designed to directly determine whether involvement modulates the effects of deception on memory. Participants were assigned randomly to either high- or low-involvement c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 36 publications
11
15
0
Order By: Relevance
“…Second, in previous studies, participants were presented with crime videos, but they were not at the crime scene and had little involvement in the incident. It has been suggested that the degree of involvement could modulate the memory undermining effect ( Li and Liu, 2021 ). Participants in high involvement conditions showed more memory disruptions and created more non-believed memories than those in low involvement conditions, and the DIF effect was found in the high but not in the low involvement conditions ( Li and Liu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, in previous studies, participants were presented with crime videos, but they were not at the crime scene and had little involvement in the incident. It has been suggested that the degree of involvement could modulate the memory undermining effect ( Li and Liu, 2021 ). Participants in high involvement conditions showed more memory disruptions and created more non-believed memories than those in low involvement conditions, and the DIF effect was found in the high but not in the low involvement conditions ( Li and Liu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…All the findings observed in these studies were statistically significant and, specifically, demonstrated that overall lying on an event leads to a detrimental effect on memory. Finally, when we looked at the limitations stated by the authors in their papers, almost all the scholars indicated as a principal issue the impossibility to completely generalize the findings in real situations due to several reasons ( Pezdek et al, 2007 ; Vieira and Lane, 2013 ; McWilliams et al, 2014 ; Harvey et al, 2017a , b ; Besken, 2018 ; Mangiulli et al, 2018 , 2019a , b ; Otgaar et al, 2018 , 2020 ; Battista et al, 2020 , 2021a ; Riesthuis et al, 2020 ; Li and Liu, 2021 ; Vo et al, 2021 ). In particular, the main reasons reported to explain this issue were (i) the use of a sample of the population (i.e., students) being not necessarily representative of the general population (ii) the stimulus adopted lacking of ecological validity.…”
Section: Discussionmentioning
confidence: 98%
“…Scholars have used different paradigms to examine the impact of lying on memory. For example, in studies on false denials (e.g., Vieira and Lane, 2013 ; Otgaar et al, 2016 , 2018 ; Battista et al, 2021a ; Li and Liu, 2021 ) researchers typically ask participants to watch some pictures or a video (i.e., mock crime) and subsequently require them to answer some questions regarding the stimulus (i.e., pictures or video) either without guessing or denying the occurrence of several experienced detail. After an interval, participants’ memory is tested through a source monitoring task and/or cued questions with the instructions to provide an honest response for all questions.…”
Section: Studying the Effects Of Lying On Memorymentioning
confidence: 99%
See 2 more Smart Citations